Theoretical approach of understanding impacts of team separation in global software development - Bondoc, Edwin Ronnel P. (Animo Repository, 2018)
© PACIS 2018. Global Software Development (GSD) refers to distributed software development in form of offshore insourcing and outsourcing. GSD promises benefits like cost-saving, time to market reduction, access to global talents, and task modularization. However, GSD encounters issues caused by team separation which has five dimensions: geographical, temporal, cultural, organizational, and work. These issues affect GSD activities. Issues reported in GSD are greater than identified solutions. Thus, it can be inferred that GSD lacks a guide on how it should be done (planned and implemented). This study aims to build a framework using open-ended inductive theory building method, to explain why GSD fail (due to team separation), and how it can succeed. The framework will be grounded in Process Virtualization, Task-Technology Fit, and Transactive Memory theories. This study will use the case study approach under phenomenological research of qualitative design to understand the phenomenon thru experiences of participants, and processes involved.